Profitability of betel leaf (Piper betle L.) cultivation in some selected sites of Bangladesh (Bangladesh Journal of Agricultural Research, 2015)
The study was conducted in four betel leaf growing areas, namely Barisal, Chittagong, Rajshahi and Kustia district during 2013-14 to assess the cultivation practices, physical productivity, profitability, and to explore the constraints to betel leaf cultivation. The study has been designed to investigate the economics of betel leaf production considering intensive cultivated areas for recent information in Bangladesh. From each district, two upazilas were selected considering the concentration of betel leaf growers and easy access. Also from each upazila, two blocks and from each block 20 farmers were selected with the consultation of Upazila Agriculture Officer and Sub Assistant Agriculture Officer. The study revealed that betel leaf cultivation was profitable in the study areas, although BCR in the first and second years was below one which was due to high initial cost. The highest yield and gross return of betel leaf cultivation were in the fifth year. The benefit cost ratio was found highest in 6-10 year followed by 5th and 11-15 year. The benefit cost ratio at 12%, 15% and 20% rate of interest were 1.27, 1.25 and 1.21 respectively. Internal rate of return (IRR) was calculated 62% in current situation, IRR 37% was found by 10% decrease of return and 39% by 10% increase of cost. The problems like leaf rot disease, high price of boroj materials, low price of betel leaf, high price of oilcake, etc. were facing by the betel leaf farmers.Bangladesh J. Agril. Res. 40(3): 409-420, September 2015